Biotin-free systems provide stronger immunohistochemical signal in oestrogen receptor evaluation of breast cancer. Issue 8 (15th May 2009) - Rocha, R M; Miller, K; Soares, F; Schenka, N; Vassallo, J; Gobbi, H
Abstract : Aims: Biotin-free polymeric visualisation systems (BFPS) were compared with streptavidin–biotin systems (SABS) in the evaluation of immunoreactivity for oestrogen receptor (ER) in breast carcinomas. Methods: The antiestrogen antibody clone SP1 was employed in a tissue microarray containing 320 breast carcinomas. Eleven different detection systems were used: six second-generation BFPS (Advance, Novolink, SuperPicTure, PicTure Max, Super Sensitive non-biotin HRP and Mouse/Rabbit Polydetector HRP/DAB), one first-generation BFP (EnVision+), and four SABS (LSAB+, EasyPath, Super Sensitive and Mouse/Rabbit Immunodetector HRP/DAB). The slides were digitalised using a Mirax scanner and the resulting images were analysed by an automated method and by visual analysis using the Allred score system considering positive nuclear staining. Cytoplasm staining was also separately evaluated. Results: The BFPS Advance and Novolink showed the highest scores by visual analysis, and additionally detected two positive cases that were considered negative using the other detection systems. Likewise, these systems, together with the SAB LSAB+, showed higher staining intensity by the automated method. BFPS revealed no cytoplasm staining, in contrast to the SABS. Conclusions: The second-generation BFPS, especially Advance and Novolink, provided stronger and sharper nuclear immunohistochemical signals as compared with most SABS, with no non-specific cytoplasm staining. In a few instances, the second-generation BFPS systems showed discordant results in relation to SABS; therefore further studies correlating these findings to therapeutic responses are necessary. BFPS may represent a high-quality tool for research and clinical evaluation of ER in breast cancer.